The Public and Leprosy Patients: A Theoretical Review of Peter L. Berger and Thomas Luckmann Social Construction - Musfirah; Shermina Oruh; Andi Agustang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The stigma of leprosy can generally be seen from two aspects, namely, self-stigma (such as shame and low self-esteem) and public stigma (such as societal prejudices), which are also related to the restriction of social participation and discrimination. Prejudice or assumptions are further reinforced by the presence of negative labels or stereotypes attached to an individual. The emergence of discriminatory actions is a result of the majority's assumptions or prejudices towards others. These assumptions or prejudices then become a form of differentiation in society. This research utilizes a qualitative method with the social construction approach of Peter L. Berger and Thomas Luckman. Data analysis is conducted in accordance with Berger's social construction theory, where social construction can be understood through the processes of externalization, objectification, and internalization. The results of this research indicate the existence of different constructions by each individual based on their level of information and experience. Firstly, society constructs leprosy patients as individuals cursed. Secondly, leprosy patients are constructed as sufferers of hereditary diseases. Thirdly, leprosy patients are constructed as sufferers of a highly contagious and dangerous disease. Fourthly, society constructs leprosy patients as individuals with a curable contagious disease.